Organization as Strategy: Restructuring Production in the Film Industry - ROBINS, James Arthur (Institutional Knowledge at Singapore Management University, 1993)
Few changes in the structure of firmas have attracted as much attention during the last decade as the movement away from integrated production and toward cooperative relations among independent organizations. Despite recent emphasis on these strategies of 'disaggregation' and 'netrork' organization, little quantitative research exists on the impact of this type of reorganization on eocnomic performance - at least in part due to the difficulty of obtaining appropriate data. Th eeconomic impact of disaggregation is examined in thi paper using data on film production in the period after World War II.